2002
DOI: 10.1103/physreve.65.066125
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic description of traffic breakdowns

Abstract: We analyze the characteristic features of traffic breakdown. To describe this phenomenon we apply to the probabilistic model regarding the jam emergence as the formation of a large car cluster on highway. In these terms the breakdown occurs through the formation of a certain critical nucleus in the metastable vehicle flow, which enables us to confine ourselves to one cluster model. We assume that, first, the growth of the car cluster is governed by attachment of cars to the cluster whose rate is mainly determi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 16 publications
0
50
0
Order By: Relevance
“…without bottleneck). Based on this approach Kühne et al [91] confirmed that the probability of the F→J transition in the metastable region is increasing with the flow rate in free flow. They applied this result to explain the breakdown phenomenon at a highway bottleneck.…”
Section: Probabilistic Theory Of Highway Capacitymentioning
confidence: 93%
“…without bottleneck). Based on this approach Kühne et al [91] confirmed that the probability of the F→J transition in the metastable region is increasing with the flow rate in free flow. They applied this result to explain the breakdown phenomenon at a highway bottleneck.…”
Section: Probabilistic Theory Of Highway Capacitymentioning
confidence: 93%
“…For a recent comprehensive discussion of the breakdown phenomenon in CA-models and in the Krauß et al model in the fundamental diagram approach see also [55,56]. The theories in [33,52,53,54,55,56] belong to the fundamental diagram approach.…”
Section: Probability Of the Breakdown Phenomenon (The F→s Transition)mentioning
confidence: 99%
“…At the microscopic level, while pair longitudinal interactions are now quite well-known [1,2,3,4,5,6,7], there is still much to learn about lateral interactions [8,9,10], and also about collective effects -or correlations between vehicles, to state it otherwise [11,12,13,14,15]. This knowledge would be useful though, both in the perspective of modelling, and of security improvement.…”
Section: Introductionmentioning
confidence: 99%